Treatment Sequencing in a Chronic Lymphocytic Leukemia Patient with Central Nervous System Involvement - Filipa Mousinho; Tatiana Mendes; Paula Sousa e Santos; Maria João Acosta; José Pereira; Maria Arroz; Cândido Silva; Ana Paula Azevedo; Rita Oliveira; Martinha Chorão; Fernando Lima (Case Reports in Hematology)
Early-stage chronic lymphocytic leukemia (CLL) with neurologic involvement is a rare condition and should require a careful follow-up. Although no standard protocol exists for this condition, intrathecal chemotherapy, combined with systemic chemoimmunotherapy, has been used previously. This case describes the treatment of a patient with CLL and symptomatic compromise of the central nervous system. Our results suggest that a combination of chemotherapy, radiotherapy, and ibrutinib, administered sequentially over a 2-year period, led to a near-complete resolution of the cerebral spinal fluid neoplastic infiltration. Importantly, this response has been maintained with ibrutinib monotherapy for more than 12 months.